Femtosecond Third-Order Non-Linear Optical Properties of Unconstrained Green Fluorescence Protein Chromophores - Ahmed, Md Soif; Biswas, Chinmoy; Banerjee, Dipanjan; Chetti, Prabhakar; Yang, Jye-Shane; Soma, Venugopal Rao; Raavi, Sai Santosh Kumar (Frontiers in Physics, 2022)
We report herein, results on the third-order nonlinear optical (NLO) properties of four structurally unconstrained green fluorescence protein (GFP) chromophores, namely 1, 2, 3 and 4. Using experimental techniques and theoretical calculations such as UV-visible spectroscopy, density functional theory (DFT), time-dependent density functional theory (TDDFT) and Z-scan techniques, we have investigated the linear absorption, ultrafast non-resonant third-order optical nonlinearities and the onset of optical limiting thresholds of these benzylidenedimethylimidazolinone (BDI) dyes. The Z-scan measurements were performed at a wavelength of 800 nm with ~70 femtosecond (fs) pulses. We have witnessed a strong reverse saturable absorption (fitted to three-photon absorption) for all of the molecules with fs pulse excitation. The valley-peak curves obtained from the closed-aperture Z-scan technique revealed the positive nonlinear refractive index (self-focusing) nature of these molecules. We have evaluated the various third-order NLO coefficients (second hyperpolarizability,  ~10-33 esu), which were found to be larger than that of similar molecules reported in recent literature.